Rancang bangun Media Pembelajaran berbasis Multimedia Interaktif Pengenalan ragam budaya Indonesia - Achmad Baijuri; Ahmad Musaddad (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2022)
MI Al Falah Pesanggrahan is one of the madrasas under the auspices of the Al Falah Pesanggrahan Islamic boarding school. This institution does not yet have learning media that can help the teaching and learning process, especially the subject of Indonesian culture. The impact of this problem has resulted in students not being entirely familiar with Indonesian culture directly, so it is necessary to design a learning media that can assist the teaching and learning process and in the end, students can easily learn Indonesian culture. In this study, the type of data collection was carried out through two kinds, namely action research and field research. Multimedia Development Life Cycle is one of the methods used to develop a system to build interactive learning media in this study. This research produces learning media products that make it easier for teachers to convey material and students easily understand Indonesian cultural lessons.